Effects of exponentially decaying and growing concentrations on particle size distribution from a scanning mobility particle sizer. Issue 10 (2nd October 2020) - Lee, Handol; Yook, Se-Jin; Ahn, Kang-Ho
Abstract: A scanning mobility particle sizer (SMPS) is one of the most widely used instruments to obtain size distribution for atmospheric particles. In an SMPS measurement, a voltage scanning process on a differential mobility analyzer is required, and it typically takes 30 s to 120 s to obtain one entire size distribution. A size distribution obtained by an SMPS measurement might have significant deviations from actual values due to the scanning process when the measured particle concentrations change over time. In this study, we introduce an analytical approach for estimating particle size distribution under exponentially decaying and growing particle concentrations. The analytical SMPS results are validated by performing experiments using exponentially decaying particle concentrations under the same conditions. Furthermore, the effects of a decay parameter, initial size distribution, and scan time are evaluated, and the deviations from actual (real or true) size distributions obtained by an exact solution are analyzed. Geometric mean diameters and standard deviations of the size distributions from SMPS results increase or decrease with exponentially decaying or growing concentrations, respectively, and total concentrations estimated by the analytical SMPS approach are significantly underestimated or overestimated compared to real total concentrations. While SMPS measurements have been widely employed in various applications such as atmospheric particle characterization in highly variable particle concentrations versus time, very few studies on the influence of changing concentrations on SMPS measurements have been conducted. Therefore, the introduced analytical approach and findings provide valuable insight into the importance of accurate SMPS measurements with changing particle concentrations. Copyright © 2020 American Association for Aerosol Research